2021
DOI: 10.3390/ijerph19010171
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and COVID-Related Predictors for Mental Health Condition of Mainland Chinese in Canada Amidst the Pandemic

Abstract: The current study investigates the mental health condition of Mainland Chinese in Canada and identifies the associated sociodemographic and COVID-19-related predictors. A sample of 471 Mainland Chinese aged 18 or older completed an online survey that collected information on demographics, experience, cognition, and behaviours related to the COVID-19 pandemic and mental health condition. Mental health condition was assessed with the Depression, Anxiety, and Stress Scale-21 (DASS-21) for the depression, anxiety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 49 publications
4
21
0
Order By: Relevance
“…Furthermore, the results also identified experienced anti-Chinese discrimination as a risk factor for higher COVID-19 peritraumatic distress (Table 2) and perceived anti-Chinese discrimination as a predictor for higher loneliness (Table 3). These findings were consistent with previous findings that increased experienced discrimination [46] and perceived discrimination [44,48] against Chinese were associated with increased distress or mental health symptoms. Specifically, experienced discrimination was significantly associated with higher levels of COVID-19 peritraumatic distress, suggesting that experiences of discrimination may add a traumatic additional layer to the negative experiences of the pandemic in Chinese residents.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the results also identified experienced anti-Chinese discrimination as a risk factor for higher COVID-19 peritraumatic distress (Table 2) and perceived anti-Chinese discrimination as a predictor for higher loneliness (Table 3). These findings were consistent with previous findings that increased experienced discrimination [46] and perceived discrimination [44,48] against Chinese were associated with increased distress or mental health symptoms. Specifically, experienced discrimination was significantly associated with higher levels of COVID-19 peritraumatic distress, suggesting that experiences of discrimination may add a traumatic additional layer to the negative experiences of the pandemic in Chinese residents.…”
Section: Discussionsupporting
confidence: 92%
“…The results also showed that participants with a poorer self-reported health status tended to show higher COVID-19 peritraumatic distress and loneliness. This replicated Yu et al [44], which identified health status as a risk factor for mental health outcomes (i.e., depression, anxiety, and stress). Participants with pre-existing health conditions were experiencing higher distress, possibly because they were at a higher risk of contracting COVID-19.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In particular, worry about personally contracting COVID-19 has been significantly associated with COVID-19 peritraumatic distress [ 33 ]. Similarly, previous research showed that perceived and experienced racial discrimination serve as robust predictors for mental health condition among Chinese living in Canada [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 65%